Transformasi Digital Teknologi Dalam Meningkatkan Industri Kreatif - Pastima Simanjuntak; Nurma Dhona Handayani (Prosiding, 2022)
The digital transformation of today's technology has brought many changes to the world of communication. Information technology is not only a tool to communicate, but also a means to make friends, share photos and even as a means of promotion for an online store business. Information technology is also a tool that has been available as a means to increase sales targets and can also be a means to find out the range of all promotional activities carried out. With this technology strategy, it will bring change to society and can encourage various efforts to change, because people are still unfamiliar with information technology and many school children and teenagers still do not understand the application of information technology and also do not understand the application of English. Therefore, the purpose of this coaching is to invite the public to know the digital transformation of technology.